Comparison of administrative/billing data to expected protocol‐mandated chemotherapy exposure in children with acute myeloid leukemia: A report from the Children's Oncology Group. Issue 7 (11th March 2015) - Miller, Tamara P.; Troxel, Andrea B.; Li, Yimei; Huang, Yuan‐Shung; Alonzo, Todd A.; Gerbing, Robert B.; Hall, Matt; Torp, Kari; Fisher, Brian T.; Bagatell, Rochelle; Seif, Alix E.; Sung, Lillian; et al.
<x xml:space="preserve">Abstract</x> Background Recently investigators have used analysis of administrative/billing datasets to answer clinical and pharmacoepidemiology questions in pediatric oncology. However, the accuracy of pharmacy data from administrative/billing datasets have not yet been evaluated. The primary objective of this study was to determine the concordance of Pediatric Health Information System (PHIS) administrative/billing chemotherapy data with Children's Oncology Group (COG) protocol‐mandated chemotherapy and to assess the implications of this level of concordance for further PHIS research. Procedure Data from 384 pediatric patients (1, 060 courses of chemotherapy) with acute myeloid leukemia treated on COG clinical trial AAML0531 were previously merged with PHIS data. PHIS chemotherapy administrative/billing data were reviewed for the first three courses of chemotherapy. Accuracy was assessed using three metrics: recognizability of chemotherapy pattern by course, chemotherapy administration pattern by individual medication, and concordance with the number of days of protocol‐defined chemotherapy. Results The chemotherapy pattern was recognizable in 87.3% of courses when course‐wide accuracy was assessed. Chemotherapy administration pattern varied by medication. Cytarabine had perfect concordance 70.9% of the time, daunorubicin had perfect concordance 77.4% of the time, and etoposide had perfect concordance 67.8% of the time. Conclusions The accuracy of chemotherapy administrative/billing data supports the continued use of PHIS data for epidemiology studies as long as investigators perform data quality control checks and evaluate each specific medication prior to undertaking definitive analyses. Pediatr Blood Cancer 2015;62:1184–1189. © 2015 Wiley Periodicals, Inc.